2021
DOI: 10.1186/s43094-021-00251-1
|View full text |Cite
|
Sign up to set email alerts
|

Traditional uses, phytochemistry and pharmacology of Bauhinia racemosa Lam.: a comprehensive review

Abstract: Background Bauhinia racemosa is not familiarly known in Asian countries due to its limited existence and lack of medicinal information. It is commonly used as a medicine, ornamental plant, fence plant, and fodder for livestock since ancient times. It is also used as a landfill tree to avoid soil erosion of the forest. Main body In South India, people cultivate this plant in their premises in order to protect themselves from the effects of thunder. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…In accordance with this statement, the antiviral drug abilities of these phytochemicals have been discussed as follows. Consistent with this statement, previous phytochemical studies showed that the catechins were found in the aerial parts of Camellia sinensis L. Prunus dulcis L, Pseudocydonia sinensis Schneid, Malus domestica Mühle, Cydonia oblonga Mühle, Bauhinia racemosa Lam, Spondias mombin L, Ricinus communis and Rumex acetosa [16,17]. Among these plants, Camellia sinensis has been found to have a higher content of catechins.…”
Section: Epicatechinsupporting
confidence: 64%
“…In accordance with this statement, the antiviral drug abilities of these phytochemicals have been discussed as follows. Consistent with this statement, previous phytochemical studies showed that the catechins were found in the aerial parts of Camellia sinensis L. Prunus dulcis L, Pseudocydonia sinensis Schneid, Malus domestica Mühle, Cydonia oblonga Mühle, Bauhinia racemosa Lam, Spondias mombin L, Ricinus communis and Rumex acetosa [16,17]. Among these plants, Camellia sinensis has been found to have a higher content of catechins.…”
Section: Epicatechinsupporting
confidence: 64%
“… Letters in the table denote references: a [ 4 ]; b [ 1 ]; c [ 5 ]; d [ 47 ]; e [ 9 ]; f [ 48 ]; g [ 10 ]; h [ 7 ]; i [ 6 ]*—only genus mentioned; j [ 49 ]; k [ 50 ]; l [ 11 ]; m [ 51 ]; n [ 52 ]; o [ 53 ]; p [ 54 ]; q [ 55 ]; • mentioned in online databases with no reference provided. …”
Section: Figurementioning
confidence: 99%
“…Quantitative analyses have previously been performed on C. fistula seed oil, reporting β-sitosterol at 62% of total sterols, followed by stigmasterol and campesterol at much lower levels [44]. ; c [5]; d [47]; e [9]; f [48]; g [10]; h [7]; i [6]*-only genus mentioned; j [49]; k [50]; l [11]; m [51]; n [52]; o [53]; p [54]; q [55]; • mentioned in online databases with no reference provided.…”
Section: Sterols and Squalenementioning
confidence: 99%
“…The BR plant with both conventional and pharmaceutical uses offers enormous therapeutic promise for treating a wide range of illnesses. Over 37 compounds have been isolated from various parts of this plant including alkaloids, steroids, triterpenoids, glycosides, tannins, saponins, phenolic compounds, flavonoids, galactolipid, and catechin. …”
Section: Introductionmentioning
confidence: 99%